ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENURUNAN LUAS LAHAN SAWAH PENGAIRAN TEKNIS DI KOTA TEGAL - , Roni Andriyanto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to identify and analyze the magnitude of the effect of the identified factors affecting the decline in rice field area in the city of Tegal technical irrigation during periods of the year 1992-2010. The data used were secondary data with the model time series. The research methodology uses statistical methods with a multiple regression analysis. Dependent variable used is the area of technical irrigation rice field while the independent variables include the total of production of paddy rice per hectare technical irrigation, paved road length, number of motorcycles, GDP per capita, the number of industries, the amount of industrial investment, the number of traditional markets, the number of modern market, the number of households, the number of health centers and hospitals, the number of elementary schools, number of junior high schools, the number of high schools and vocational education, the number of colleges, and the number of direct expenditure of government. Based on the analysis found that during periods of the year 1992-2010, a factor which has positive and statistically significant of technical irrigation rice field area covering factor of the number of junior high schools, the number of high schools and vocational education, paved road length, the amount of industrial investment, and the number of direct expenditure of government. Factors that affect negatively and statistically significant factors include the number of modern markets, number of motorcycles, GDP per capita, and total production of paddy rice per hectare technical irrigation. Magnitude of the effect of each factor to the average of the mean technical irrigation rice field area: factor of the number of junior high school 1.469192, factor of the number of high schools and vocational education 0.586167, factor of paved road length 0.464423, factor of the amount of industrial investment 0.090499, factor of the number of direct expenditure of government 0.027839, factor of the modern market -0.480072, factor of the number of motorcycle -0.151098, factor of GDP per capita -0.144269, and factors of total production of paddy rice per hectare technical irrigation - 0.085264.